PATH-32. GENOMIC LANDSCAPE AND BIOLOGY OF MEDULLOBLASTOMA IN ADULTS. (11th November 2019) - Goschzik, Tobias; zur Mühlen, Anja; Dörner, Evelyn; Waha, Andreas; Friedrich, Carsten; Hau, Peter; Pietsch, Torsten
Abstract: BACKGROUND: Medulloblastoma (MB) is a rare disease in adults. Only few cohorts have been studied so far. METHODS: Histological features were evaluated and tumors were annotated to WNT-MB, SHH-MB, and non-WNT/non-SHH-MB by immunohistochemistry. Copy number alterations were analyzed by genome-wide molecular inversion probe array. MB-related genes were screened by NGS panel and Sanger sequencing in WNT- and SHH-MB. RESULTS: The cohort of 117 tumors contained 14.5% WNT-MB, 63.2% SHH-MB, and 22.2% non-WNT/non-SHH-MB. Classic histology was found in WNT-MB, non-WNT/non-SHH-MB and 22% of SHH-MB; 78% of SHH-MB showed desmoplastic/nodular histology. In WNT-MB, CTNNB1 mutations were found in 88.2% and monosomy 6 in 52.9% of cases. In SHH-MB, PTCH1 mutations were present in 40% of cases and chromosome 9q loss including the PTCH1 locus was the most frequent copy number event in SHH-MB (50%), while SMO and SUFU mutations were found only in 15.4% and 7.7%, respectively. TERT promoter mutations were present in 92.3% of SHH-MBs. Only 2 (3%) of SHH-MB were TP53 -mutated (1.7% of whole cohort). In non-WNT/non-SHH-MB, isochromosome 17q was the most frequent chromosomal alteration (84.6%). A previously published whole chromosomal aberration (WCA) signature with ≥1 WCA was found in 69.2% of cases. For 87 cases, survival data were available. WNT-MB, SHH-MB with wildtype TP53 and non-WNT/non-SHH-MB showed similar outcomes (5-year OS: 75%, 78.1% and 69.1%, respectively). Both SHH-MB patients with mutant TP53 died of disease. Patients with non-WNT/non-SHH-MB characterized by the cytogenetic WCA phenotype showed – as described in pediatric standard-risk MB – significant better overall survival compared to patients with tumors lacking WCA (p=0.02). CONCLUSIONS: Adult MB represents four defined biological/genomic entities. While in our cohort WNT-MB and SHH-MB- TP53 wt were standard risk, non-WNT/non-SHH-MB patients could be divided into two risk-groups according to the presence or absence of WCA in the tumors as previously published for childhood standard-risk MB.